2013
DOI: 10.1093/toxsci/kft025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of De Novo Catecholamine Synthesis in Mediating Methylmercury-Induced Vesicular Dopamine Release From Rat Pheochromocytoma (PC12) Cells

Abstract: The purpose of this study was to characterize methylmercury (MeHg)-induced dopamine (DA) release from undifferentiated pheochromocytoma (PC12) cells and to examine the potential role for DA synthesis in this process. MeHg caused a significant increase in DA release that was both concentration- and time-dependent. DA release was significantly increased by 2µM MeHg at 60min and by 5µM MeHg at 30min; 1µM MeHg was without effect. Because DA release induced by 5µM MeHg was associated with a significant percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The concentration of dopamine at the synapse resulting from the cumulative activity of the aforementioned regulatory mechanisms, rather than overall tissue concentrations, ultimately influences the activity of dopaminergic neurons. Multiple studies have demonstrated increased presynaptic release of dopamine from brain tissue in rats, mice, and rat PC‐12 cell lines following MeHg exposure . In addition, the results of the present study show significant decreases in MAO activity in eggs incubated with MeHg concentrations as low as 0.048 ppm compared with controls (ANOVA, df = 5, F = 9.43, p < 0.01) .…”
Section: Resultssupporting
confidence: 65%
“…The concentration of dopamine at the synapse resulting from the cumulative activity of the aforementioned regulatory mechanisms, rather than overall tissue concentrations, ultimately influences the activity of dopaminergic neurons. Multiple studies have demonstrated increased presynaptic release of dopamine from brain tissue in rats, mice, and rat PC‐12 cell lines following MeHg exposure . In addition, the results of the present study show significant decreases in MAO activity in eggs incubated with MeHg concentrations as low as 0.048 ppm compared with controls (ANOVA, df = 5, F = 9.43, p < 0.01) .…”
Section: Resultssupporting
confidence: 65%
“…MeHg has been reported to both facilitate and suppress exocytosis 17 34 35 . In addition, we recently reported that microglia release ATP by exocytosis via a vesicular nucleotide transporter (VNUT)-mediated pathway(s) 11 ; thus, we next investigated VNUT-mediated ATP release evoked by MeHg.…”
Section: Resultsmentioning
confidence: 99%
“…MeHg-induced disruptions in choice co-occur with increased sensitivity to dopamine transporter (DAT) blockers, such as d -amphetamine (Rasmussen & Newland, 2001) and cocaine (Reed & Newland, 2009). Further, MeHg inhibits DAT (Dreiem, Shan, Okoniewski, Sanchez-Morrissey, & Seegal, 2009) and stimulates DA efflux both in vitro (Tiernan, Edwin, Goudreau, Atchison, & Lookingland, 2013) and in vivo (Faro, Do Nascimento, San José, Alfonso, & Durán, 2000). …”
mentioning
confidence: 99%